PENGARUH GAME EDUKASI "MATEMATIKA SERU" TERHADAP PEMAHAMAN KONSEP OPERASI HITUNG DASAR SISWA KELAS III - Melviana, Melviana; Irawati, Riana; Isrok'atun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using the educational game “Matematika Seru” on the understanding of basic arithmetic concepts among third-grade elementary school students. The research method used is a quasi-experimental design with a pretest-posttest control group. The population for this study was all elementary schools in the Sumedang Utara subdistrict, and the sample consisted of SD Negeri Rancapurut, which had 60 third-grade students. The students were divided into two groups: the experimental group, which used the educational game, and the control group, which used conventional methods. Data were collected through validated tests with sufficient reliability. Data analysis was conducted using normality tests, homogeneity tests, paired t-tests, and mean difference tests using SPSS Statistics 24 software. The results of the study indicate a positive effect on the understanding of basic arithmetic operations among third-grade students who used the educational game “Matematika Seru” with an N-Gain of 0.51 and in conventional learning with an N-Gain of 0.27. Additionally, there was a significant difference in the effect between students using the educational game “Matematika Seru” and conventional learning on posttest scores. This is demonstrated by the Effect Size calculation with a Cohen's d value of 1.445, which falls into the category of a large effect size.